HUKUM DAN PERADILAN DALAM MASYARAKAT MUSLIM PERIODE AWAL ISLAM - Marzuki, Marzuki (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
This paper deals with law and Islamic court in the period of Prophet an Khulafā’ Rāshidun. In the period of Prophet, law was not widely interpreted since the Prophet was the only source at that time. There was also also no building for the court, but dispute resolution was held in the mosque. In the period of Khulafā’ Rāshidun, especially in ‘Umar’s period, there was a separation betweem legislative, executive, and judicative bodies. There was also building for court, in ‘Uthman’s period, and salaries were given to the judges from Bayt al-Mal. In. ‘Ali’s period, administration of justice began to be independent in solving the case.